The Effect of Job Insecurity and Minimum Wage on Labor Productivity in the Formal Sector - Sesario, Revi (Nomico, 2026)
Labor productivity is a key driver of economic growth, yet Indonesia continues to face structural challenges related to wage policy and employment stability. This study aims to analyze the effect of minimum wage and job insecurity on labor productivity in Indonesia’s formal sector. Using a quantitative explanatory approach, the study combines secondary provincial data with primary survey data measuring perceived job insecurity. Multiple linear regression analysis, including an interaction term, is applied to examine both direct and moderating effects. The results show that minimum wage has a positive and significant effect on labor productivity, while job insecurity has a negative effect. Furthermore, job insecurity weakens the positive relationship between minimum wage and productivity, indicating that employment instability reduces the effectiveness of wage policy. These findings highlight that productivity outcomes are influenced not only by economic factors but also by employment conditions and institutional quality. The study concludes that minimum wage policy can enhance productivity when supported by stable employment conditions and effective regulatory enforcement. Without employment security, wage increases may produce limited or inconsistent productivity gains. Therefore, an integrated policy approach that combines wage regulation, employment protection, and institutional strengthening is essential to achieve sustainable productivity growth in Indonesia’s formal sector.